Pemanfaatan Aplikasi TikTok Sebagai Sarana Kegiatan Aktivisme Digital tentang Perlindungan Data melalui Akun @SEJIWA.foundation - Muhamad Isnaini; Krisjodie Julio (Universitas Muhammadiyah Surakarta, 2024)
The SEJIWA Foundation created a digital activism movement by creating video content on TikTok about personal data theft in Indonesia, aiming to share information about how to avoid online fraud and overcome the problems that occur online fraud. Conveyed through social media content creators consisting of TikTok user actors with the account name @SEJIWA.foundation with theme of digital literacy in online fraud causes theft of personal data. This study aims to obtain information regarding the background of digital activism movement content creation in depth, starting from who are the actors involved in creating @SEJIWA.foundation TikTok video content to the dynamics of the digital activism movement in the @SEJIWA.foundation account regarding online fraud and theft of personal data. Also to find out about what form of personal data theft that takes many victims and how to prevent it through the use of new media concepts in carrying out digital activism activities, with TikTok social media @SEJIWA.foundation account. This research uses virtual ethnographic methods to explain the digital activism movement by utilizing the social media TikTok. The results of this research shows that dynamics are obtained by carrying out the digital activism movement itself. Where making movements will increase the dynamics or power of knowledge. Starting digital activism activities is the process of providing the dynamics or power of knowledge to social communities to avoid the rise of crimes. Because this knowledge will not mean anything if it is kept hidden and not shared with others.